Experience of treatment of prosthetic valve endocarditis: a retrospective single-center cross-sectional study - Andrade, Matheus de Oliveira; Raffoul, Gabriel Elias Salmen; Macedo, Murilo Teixeira; Silva, Claudia Neto Gonçalves Neves da; Teixeira, Maria Aparecida Santos; Pontes, Sônia Jaciara Neto; Daher, Mauricio; Daher, Mauricio; Cunha, Claudio Ribeiro da; Atik, Fernando Antibas (São Paulo Medical Journal, 2018)
BACKGROUND: The aim of this study was to describe the experience of treatment of early prosthetic valve endocarditis at a heart center. DESIGN AND SETTING: Retrospective single-center study on data collected from electronic medical records covering the period from January 2009 to December 2015. METHODS: Over the study period, 1,557 consecutive valve operations were performed on adult patients. The study population comprised 32 patients (2%) who were diagnosed with prosthetic valve endocarditis within 12 months after the index surgery. Medical records were retrieved from electronic hospital records, retrospectively. Descriptive clinical, echocardiographic, microbiological and treatment-type data were used. Risk factors for early mortality were studied through univariate and multivariate analyses. RESULTS: The main clinical manifestation of infective endocarditis was fever, and this was present in all patients. Most of the prostheses were affected in the aortic position (40.6% of cases). The most commonly cultured microorganisms were Staphylococcus epidermidis and Staphylococcus aureus. Twenty-six patients (81.3%) underwent surgical treatment and six (18.7%) underwent exclusive clinical treatment. The prevalence of postoperative complications was 31.3% and hospital mortality occurred in seven cases (21.9%). The mortality rate was 50% among the patients who underwent medical treatment and 15.4% among those who underwent surgery. There were no independent risk factors for mortality. CONCLUSION: Prosthetic valve endocarditis is an infrequent complication of valve replacement. Surgical treatment has mortality rates compatible with the severity of patients’ conditions. Surgical indication should not be delayed when clinical treatment has been ineffective.